Posiedzenia Komisji Bizantynologicznej Polskiego Towarzystwa Historycznego (KB PTH) w roku akademickim 2024/2025 - Kochanek, Piotr (Vox Patrum, 2025)
Report from the meetings of the Byzantine Commission of the Polish Historical Society in the Academic Year 2024/2025.